Influence of the carving ski on muscle activity - a comparison with the conventional ski using surface electromyography - Taniguchi, K.; Katoh, M.; Katayose, M. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Recently, a new type of ski called a carving ski has become extremely popular. However, little scientific data exists regarding the effect of these skis on certain human factors. This study was designed to compare the muscular activity during skiing on two types of carving skis {skis with moderate sidecut; CARV1 and with large sidecut; CARV2) and the conventional alpine ski (CON) using quantitative Parameters of electromyography (EMG).